EP566 Location of sentinel lymph nodes in endometrial cancer in a series of 207 patients with dual tracer injection in cervix and uterine fundus. (1st November 2019) - Mancisidor, M; Mateos, C; Ruiz, R; Gorostidi, M; Rezola, M; Lekuona, A
Abstract : Introduction/Background: Sentinel lymph node biopsy (SLNB) in endometrial cancer is not standardized yet. Multiple studies have been published using different tracers and injection sites. Most autors prefer cervix injection because of its simplicity, reproducibility and high detection rate, despite detecting few sentinel lymph nodes (GC) in the aortic area. We present our data on location of GCs injecting the green indocyanine tracer (ICG) into both the cervix and uterine fundus in order to increase the detection of GC in the aortic area. Methodology: We included 207 patients intervened from 2014 to 2018. We injected 2 ml of ICG into the uterine fundus through the cervix and another 4 ml in the cervix, 2 ml at 9 o'clock and 2 ml at 3 o´clock. Then we locate and selectively biopsy the GC, first in the aortic area, after in the pelvic area. We established 10 aortic zones (laterocavo, precavo, interaortocavo, preaortic and lateroaortic, at supramesenteric and inframesenteric zones) and 11 pelvic zones (common iliac, external iliac, interiac, obturator, and pararectal at right and left hemipelvis and also presacral zone). We consider as positive GC macrometastases, micrometastases or isolated tumor cells. Results: We found 822 GC, 525 pelvic (64%) and 297 aortic (36%). Detection rate was 89.9%, 65.7% and 64.3% for unilateral pelvic, bilateral pelvic and aortic respectively. Of the 60 positive GC, 38 were pelvic and 22 aortic. 7.3% of GC were positive, similar in both areas (7.24% and 7.4%). Conclusion: We found less GC in the aortic than pelvic area, even injecting the tracer also in the uterine fundus. However, the percentage of positive GCs in both areas was similar. These data reaffirm the importance of studying the aortic area when performing BGC in endometrial cancer and also injecting the tracer in the uterine fundus to obtain significant detection rates. Disclosure: Nothing to disclose.